2021
DOI: 10.1002/aur.2577
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive correlates of autism spectrum disorder symptoms

Abstract: Due to the diverse behavioral presentation of autism spectrum disorder (ASD), identifying ASD subtypes using patterns of cognitive abilities has become an important point of research. Some previous studies on cognitive profiles in ASD suggest that the discrepancy between verbal intelligence quotient (VIQ) and performance IQ (PIQ) is associated with ASD symptoms, while others have pointed to VIQ as the critical predictor. Given that VIQ is a component of the VIQ-PIQ discrepancy, it was unclear which was most dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…This disrupted organization may lead to ASD subjects from small-world network to random network [ 30 , 31 ]. For the positive correlation between lambda and verbal IQ, higher verbal IQ represents milder clinical symptoms of ASD impairment [ 32 34 ]. Given lambda is positively related to the shortest path length, the positive correlation between lambda and verbal IQ may also suggest disrupted functional segregation and long-range integration.…”
Section: Discussionmentioning
confidence: 99%
“…This disrupted organization may lead to ASD subjects from small-world network to random network [ 30 , 31 ]. For the positive correlation between lambda and verbal IQ, higher verbal IQ represents milder clinical symptoms of ASD impairment [ 32 34 ]. Given lambda is positively related to the shortest path length, the positive correlation between lambda and verbal IQ may also suggest disrupted functional segregation and long-range integration.…”
Section: Discussionmentioning
confidence: 99%
“…In order to examine how cognitive ability may impact symptom presentation, we considered the influence of verbal and non-verbal IQ in our sex/gender models of ASD. Prior research has suggested that cognitive profiles are affected by an individual’s pattern of performance in verbal and nonverbal reasoning - such that an IQ “discrepancy” or “split,” (e.g., NVIQ > VIQ or VIQ >NVIQ) may serve as a potential autism-related phenotype (Black, Wallace, Sokoloff, & Kenworthy, 2009; Chapman et al, 2010); sex- and age-based differences in cognitive discrepancy profiles have also been reported in ASD (Ankenman, Elgin, Sullivan, Vincent, & Bernier, 2014; Johnson et al, 2021). In an effort to control for IQ discrepancies that often occur when comparing autistic males and females, we included a subgroup of male participants (MM) matched individually to the smaller female sample by IQ and AGE.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a lower PRI score also predicted social skill improvement ( p < 0.001), meaning that a profile of a high VCI that offset a poorer PRI to yield an overall strong FSIQ predicted social skill improvement. Specific to autism, it has been recently observed that autistic individuals with higher verbal ability demonstrate lower levels of autistic symptoms ( 37 ). Consequently, reduced autism symptoms observed in cognitive profiles with higher VCI may explain the present findings.…”
Section: Discussionmentioning
confidence: 99%
“…As described by Kimpton ( 35 ), individuals with this cognitive profile are often diagnosed with a non-verbal learning disability and experience higher rates of social skill difficulties ( 35 ). This cognitive profile also has implications for the autistic community as autistic individuals with higher verbal ability demonstrate lower levels of autistic symptoms ( 37 ) and those with lower verbal and higher non-verbal ability demonstrate increased autism symptoms ( 38 ). Despite these findings, the complex interplay between intelligence and social skills is largely unknown.…”
Section: Intelligence and Social Skillsmentioning
confidence: 99%